Clinical significance of MUC13 in pancreatic ductal adenocarcinoma. Issue 6 (June 2018) - Khan, Sheema; Zafar, Nadeem; Khan, Shabia S.; Setua, Saini; Behrman, Stephen W.; Stiles, Zachary E.; Yallapu, Murali M.; Sahay, Peeyush; Ghimire, Hemendra; Ise, Tomoko; Nagata, Satoshi; Wang, Lei; et al.
Abstract: Background: Poor prognosis of pancreatic cancer (PanCa) is associated with lack of an effective early diagnostic biomarker. This study elucidates significance of MUC13, as a diagnostic/prognostic marker of PanCa. Methods: MUC13 was assessed in tissues using our in-house generated anti-MUC13 mouse monoclonal antibody and analyzed for clinical correlation by immunohistochemistry, immunoblotting, RT-PCR, computational and submicron scale mass-density fluctuation analyses, ROC and Kaplan Meir curve analyses. Results: MUC13 expression was detected in 100% pancreatic intraepithelial neoplasia (PanIN) lesions (Mean composite score: MCS = 5.8; AUC >0.8, P  < 0.0001), 94.6% of pancreatic ductal adenocarcinoma (PDAC) samples (MCS = 9.7, P  < 0.0001) as compared to low expression in tumor adjacent tissues (MCS = 4, P  < 0.001) along with faint or no expression in normal pancreatic tissues (MCS = 0.8; AUC >0.8; P  < 0.0001). Nuclear MUC13 expression positively correlated with nodal metastasis ( P  < 0.05), invasion of cancer to peripheral tissues ( P  < 0.5) and poor patient survival (P  < 0.05; prognostic AUC = 0.9). Submicron scale mass density and artificial intelligence based algorithm analyses also elucidated association of MUC13 with greater morphological disorder ( P  <  0.001 ) and nuclear MUC13 as strong predictor for cancer aggressiveness and poor patient survival. Conclusion: This study provides significant information regarding MUC13 expression/subcellular localization in PanCa samples and supporting the use anti-MUC13 MAb for the development of PanCa diagnostic/prognostic test.